Living at the Extremes: Extremophiles and the Limits of Life in a Planetary Context - Merino, Nancy; Aronson, Heidi S.; Bojanova, Diana P.; Feyhl-Buska, Jayme; Wong, Michael L.; Zhang, Shu; Giovannelli, Donato (Frontiers in Microbiology, 2019)
Prokaryotic life has dominated most of the evolutionary history of our planet, evolving to occupy virtually all available environmental niches. Extremophiles, especially those thriving under multiple extremes, represent a key area of research for multiple disciplines, spanning from the study of adaptations to harsh conditions, to the biogeochemical cycling of elements. Extremophile research also has implications for origin of life studies and the search for life on other planetary and celestial bodies. In this article, we will review the current state of knowledge for the biospace in which life operates on Earth and will discuss it in a planetary context, highlighting knowledge gaps and areas of opportunity.